2019
DOI: 10.1016/j.surfcoat.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sputtering pressure on the surface topography, structure, wettability and tribological performance of DLC films coated on rubber by magnetron sputtering

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Diamond-like carbon (DLC) films have garnered considerable interest as materials for lubrication and protection, due to the combination of relatively high hardness, ultralow friction, and excellent wear resistance [7][8][9]. Beyond that, DLC films not only possess promising chemical compatibility with the rubber (to prevent the degradation of rubber components) but the deposition temperature can be adjusted to be lower than the upper temperature limit of the rubber (by the choice of the deposition method and controlling process variables) [10][11][12][13]. Therefore, DLC films prepared on the rubber surface is undoubtedly a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond-like carbon (DLC) films have garnered considerable interest as materials for lubrication and protection, due to the combination of relatively high hardness, ultralow friction, and excellent wear resistance [7][8][9]. Beyond that, DLC films not only possess promising chemical compatibility with the rubber (to prevent the degradation of rubber components) but the deposition temperature can be adjusted to be lower than the upper temperature limit of the rubber (by the choice of the deposition method and controlling process variables) [10][11][12][13]. Therefore, DLC films prepared on the rubber surface is undoubtedly a viable option.…”
Section: Introductionmentioning
confidence: 99%
“…3(b), it can be found that DLC film is conducive to reduce surface energy of NBR, and the DLC film prepared with the increasingly hydrogenated CH 4 gas discharge plasma possesses lower surface energy. As reported by Wen's group, lower surface energy is conducive to the aggregation of carbon atoms and the formation of films, thereby promoting the drop of film roughness [35]. Furthermore, previous studies indicated that the sp 3 rich phase surfaces of DLC films exhibited lower CA than sp 2 rich phase surfaces [41].…”
Section: Resultsmentioning
confidence: 74%
“…There is a significant difference between virgin and DLC-coated NBR that all deposited DLC films exhibit a "cauliflowerlike" morphology and have higher surface roughness than that of virgin NBR substrate. It is well known that the depression on NBR surface is a predominant position where activated carbon particles gather [35]. In this work, the virgin NBR rubber is smooth and the exposed depressions are evenly distributed and discrete.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, there are some shortcomings such as high intrinsic stress, poor adhesion strength between the film and substrate, and unstable tribological properties, which limit their further development [9][10][11][12][13]. Most of the previous studies in recent years investigated the effect of deposition temperature [14], sputtering power [15,16], deposition pressure [16], and substrate material [17] on the tribological behavior of hydrogen-free diamond-like carbon coating. Few studies [2,18] have been found on the relationship between film thickness and tribological properties of DLC coatings, and the tribological properties of ultra-thick (more than 1 µm) DLC coating deposited by HiPIMS technique remain unclear.…”
Section: Introductionmentioning
confidence: 99%